80 Smarca4 inactivation defines a subset of undifferentiated uterine sarcomas with rhabdoid and small cell features and germline mutation association. (18th September 2019) - Lin, D; Allen, J; Hecht, J; Killian, J; Ngo, N; Edgerly, C; Severson, E; Ali, S; Erlich, R; Ramkissoon, S; Vergilio, JA; Ross, J; et al.
Abstract : Objectives: A rare subset of aggressive SMARCA4 -deficient uterine sarcomas ( SMARCA4 -DUS) has been recently proposed, with only a limited number of cases having been previously described. Since potential targeted therapies exist for SMARCA4 -defficient tumors, we sought to validate and expand the clinicopathological and molecular features of SMARCA4 -DUS. Methods: A retrospective database search of a large, CLIA-certified and CAP-accredited, reference molecular laboratory was performed for clinically advanced uterine sarcomas with genomic profiles that contained SMARCA4 mutations. Clinicopathological data were extracted from patient records Morphological and molecular features were centrally reviewed. Results: Here, we identify and describe the clinicopathological and genomic features of 17 additional cases of SMARCA4 -DUS. Median patient age was 51 years (range 33–70). Most tumors were aggressive with distant metastasis. SMARCA4 -DUS demonstrated predominantly rhabdoid or large epithelioid cells with abundant cytoplasm, but also had varying degrees of small cell and spindle cell morphology. Tumors were microsatellite stable and exhibited no other or only few co-occurring genomic alterations by comprehensive genomic profiling. We discovered one patient, who developed SMARCA4 -DUS at age of 55, had a germline SMARCA4 mutation, whose daughter had previously died of small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), at the age of 32. Conclusions: Our data support the notion that SMARCA4 inactivation is the driver oncogenic event of a morphologically and molecularly distinct form of uterine sarcoma. Identification of SMARCA4 -DUS may be clinically important due to their aggressive behavior, germline association and emerging targeted therapies.